Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Section 9.7 - Common Logarithms, Natural Logarithms, and Change of Base - Exercise Set: 71

Answer

$x=-6$ and $x=-1$

Work Step by Step

We are given the equation $x^{2}+7x=-6$. Add 6 to both sides to get all terms on one side. $x^{2}+7x+6=0$ We know that 1 and 6 are factors of 6 and the sum of 1 and 6 is 7, which is the coefficient on the middle term. Therefore, the equation can be factored into the form $(x+1)(x+6)$. Set both terms equal to 0 $x+1=0$ Subtract 1 from both sides. $x=-1$ $x+6=0$ Subtract 6 from both sides. $x=-6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.